Critical process parameters evaluation of modified nanoprecipitation method on lomustine nanoparticles and cytostatic activity study on L132 human cancer cell line - Mehrotra A.; Pandit J.K. (My University, 2025)
This work was focused on identification and evaluation of process parameters of modified nanoprecipitation method, for fabrication of lomustine nanoparticles, with the aim of reducing cancer cell viability at low concentration of lomustine. The parameters controlling particle size, mostly in nanosize, were solvent/nonsolvent composition and emulsification speed of homogenizer along with aqueous phase volume. This controlled particle size is below 250 nm. The stabilizer concentration controlled particle size is within 68 nm ± 0.89 to 137 ± 0.94 nm with PDI 0.06 ± 0.008 to 0.25 ± 0.001. But, the stabilizer addition mode showed more uniform size distribution with PDI 0.085 ± 0.004. Entrapment efficiency was maintained well above 47 ± 0.23%. The drug release pattern was monophasic with controlled release over 24 hrs. In the method used, drug content was affected by ratio of polymer to drug to organic solvent, as well as homogenization speed and time. Percentage viable cells of L132 human lung cancer cell line remained, were only 5% at 100 μg/ml lomustine equivalent PLA nanoparticles. © 2012 Mehrotra A, et al.